Development and validation of an ultra‐fast and sensitive microflow liquid chromatography‐tandem mass spectrometry (MFLC‐MS/MS) method for quantification of LSD and its metabolites in plasma and application to a controlled LSD administration study in humans. Issue 5 (10th August 2016) - Steuer, Andrea E.; Poetzsch, Michael; Stock, Lorena; Eisenbeiss, Lisa; Schmid, Yasmin; Liechti, Matthias E.; Kraemer, Thomas
Abstract : Lysergic acid diethylamide (LSD) is a semi‐synthetic hallucinogen that has gained popularity as a recreational drug and has been investigated as an adjunct to psychotherapy. Analysis of LSD represents a major challenge in forensic toxicology due to its instability, low drug concentrations, and short detection windows in biological samples. A new, fast, and sensitive microflow liquid chromatography (MFLC) tandem mass spectrometry method for the validated quantification of LSD, iso‐LSD, 2‐oxo 3‐hydroxy‐LSD (oxo‐HO‐LSD), and N ‐desmethyl‐LSD (nor‐LSD) was developed in plasma and applied to a controlled pharmacokinetic (PK) study in humans to test whether LSD metabolites would offer for longer detection windows. Five hundred microlitres of plasma were extracted by solid phase extraction. Analysis was performed on a Sciex Eksigent MFLC system coupled to a Sciex 5500 QTrap. The method was validated according to (inter)‐national guidelines. MFLC allowed for separation of the mentioned analytes within 3 minutes and limits of quantification of 0.01 ng/mL. Validation criteria were fulfilled for all analytes. PK data could be calculated for LSD, iso‐LSD, and oxo‐HO‐LSD in all participants. Additionally, hydroxy‐LSD (HO‐LSD) and HO‐LSD glucuronide could be qualitatively detected and PK determined in 11 and 8 subjects, respectively. Nor‐LSD was only sporadically detected. Elimination half‐lives of iso‐LSD (median 12 h) and LSD metabolites (median 9, 7.4, 12, and 11 h for oxo‐HO‐LSD, HO‐LSD, HO‐LSD‐gluc, and nor‐LSD, respectively) exceeded those of LSD (median 4.2 h). However, screening for metabolites to increase detection windows in plasma seems not to be constructive due to their very low concentrations. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Lysergic acid diethylamide (LSD) is a semi‐synthetic hallucinogen that gained popularity as a recreational drug due to its psychedelic effects. Analysis of LSD represents a major challenge in forensic toxicology due to its known instability, low drug concentrations and short detection windows in biological samples. A new, fast and sensitive microflow liquid chromatography (MFLC) tandem mass spectrometry method allowed for validated quantification of LSD, iso‐LSD and LSD metabolites. Pharmacokinetic parameters could be determined in humans after controlled LSD administration.